Reliability of a widely used test of peripheral cutaneous vibration sensitivity and a comparison of two testing protocols. Issue 9 (September 1988) - Gerr, F E; Letz, R
Abstract : Quantitative, non-invasive instruments for assessing peripheral sensory function are being used in many epidemiological investigations of workplace hazards. To be useful in this context such tests should have high reliability and short administration time. The reliability and time efficiency of two testing protocols for determining cutaneous vibration sensitivity (vibration threshold) were compared in 22 healthy volunteers. Both methods were administered using a widely used testing device (Vibratron II). The first testing protocol was a two alternative "forced choice" method recommended by the instrument manufacturer. The second protocol was a "yes-no" method of limits procedure. Each subject's dominant index finger was tested with both methods on two occasions to compare their reliability. In these well educated subjects the method of limits procedure was found to be substantially more reliable and was much less time consuming than the recommended forced choice procedure. The simpler method of limits procedure may be preferable to the forced choice method in certain test conditions.